2000
DOI: 10.1016/s0277-9536(99)00363-9
|View full text |Cite
|
Sign up to set email alerts
|

Career preferences and the work–family balance in medicine: gender differences among medical specialists

Abstract: In this article career preferences of medical specialists in the Netherlands are analysed, based on a survey among the members of medical associations of ®ve specialties. Four di erent career preferences were o ered, each of which implied a possible variation in working hours. A questionnaire was sent to a random selected group of working specialists in general practice, internal medicine, anaesthesiology, ophthalmology and psychiatry. Logistic regressions were used to predict career preferences. Besides indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 8 publications
4
95
0
8
Order By: Relevance
“…On the other hand, women seem to place less emphasis than men on medicine as a highly paid and high-status profession (Neittaanmäki et al 1993). Nonetheless, young male physicians also seem to favour part-time work more than older physicians (Heiligers & Hingstman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, women seem to place less emphasis than men on medicine as a highly paid and high-status profession (Neittaanmäki et al 1993). Nonetheless, young male physicians also seem to favour part-time work more than older physicians (Heiligers & Hingstman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently in The Netherlands, part-time medical practice has become a favorite strategy to combine work and family duties. 5 Using data from large cross-sectional surveys of physician, we report on a culture in which part-time medical practice is uncommon and nontraditional (United States) and a medical culture in which parttime medical practice is both common and accepted (The Netherlands). These two unique datasets provide an opportunity to use physician-generated information to explore the implications of the potential increase in U.S. physicians desiring and choosing part-time careers.…”
mentioning
confidence: 99%
“…For men, the percentage grew by a similar amount from 28 percent to 45 percent." Also, Heiligers et al (2000) found that 50 percent of their sample of male and female specialists in the Netherlands expressed a preference for part-time hours. The sense that norms will only change if both genders re-prioritize work and family was echoed by many of our interviewees.…”
Section: Discussionmentioning
confidence: 99%